SISTEM INFORMASI PENGOLAHAN DATA DI DINAS PERHUBUNGAN KOTA JAMBI: Information System, Data Processing, Locally Generated Revenue, Transportation Office of Jambi City, Adobe Dreamweaver, and MySQL - Mulyati, Sri; Ade Wiguna, Seta (JURNAL AKADEMIKA, 2019)
The Transportation Office of Jambi City is one of the Regional Government Technical Offices, especially in the Jambi City area. One of the main tasks and functions is to have the authority to collect regional levies. In this research, an Information System for Data Processing of Locally Generated Revenue in Transportation Office of Jambi City is expected to be able to facilitate the data processing process until the process of recapitulation of local revenue reports at the Jambi City Transportation Agency. This application is built using Adobe Dreamweaver tools and MySQL Database. The research method used in this thesis is the waterfall method, and system modeling uses Data Flow Diagram (DFD) modeling.